Storing information of network device : lightweight directory access protocol (LDAP) as network information service / Mohd Shahirul Ikhmal Raimi - Raimi, Mohd Shahirul Ikhmal (2013)
This paper describe about the lightweight directory access protocol (LDAP) as network information service which is about development of a directory to store information of UITM Cisco devices. Nowadays, directory is having more data that static compare to database which the data can change frequently. The objective is to create LDAP directory to store information of cisco network device. This project will be developed according to three modules. First the module is to capture and decode the packet. Secondly, this project is about to store the cisco device information into the LDAP directory and lastly visualize the data through the cisco network device information webpage. In second module, LDAP directory will be develop to store data of Cisco device information in the UITM. Apache directory studio software will be used to develop this directory which is it will be installed in the microsoft window to develop the device directory. To develop this directory, schema of the directory need to be designed before it can be developed. There are three basic concepts that must be included when designing the schema which are an entry, object class and attributes. When create an entry its data content are contained in attributes, which are grouped into object class. Next, after the directory has been developed it will receive the data which contain device ID, IP address, port ID, platform and version from the first modules, the information will be extracted and then will it will specify the entry path of the data. Next, the information will be stored into LDAP directory by following the object class. For a conclusion, LDAP is not used only for authentication and store information in the directory but it can be used for many other purposes.